The Odyssey of Homer - Vandiver, Elizabeth, 1956-; Teaching Company (Chantilly, VA : Teaching Co., 1999)
In the sequel to her course, "Iliad," Dr. Vandiver explores the story of Odysseus, "the man of many twists and turns." Odysseus returns home from the Trojan War by the most winding and adventurous route imaginable, battling gods and monsters and even visiting Hades in his quest to get to Ithaca and set his lands and life in order.
lecture 1. Heroes' homecoming -- lecture 2. Guests and hosts -- lecture 3. A goddess and a princess -- lecture 4. Odysseus among the Phaiakians -- lecture 5. Odysseus tells his own story -- lecture 6. From Persephone's land to the Island of Helios -- lecture 7. The goddess, the swineherd, and the beggar -- lecture 8. Reunion and return -- lecture 9. Odysseus and Penelope -- lecture 10. Recognitions and revenge -- lecture 11. Reunion and resolution -- lecture 12. The Trojan War and the archaeologists.
Accompanying course guidebook entitled, "The Odyssey of Homer" includes outlines and bibliographical references.
DVD, region 1.
Elizabeth Vandiver, lecturer.
"Part 1 of 1"--Cover.
Keywords: Homer; Homer -- Criticism and interpretation; Epic poetry, Greek -- History and criticism; Odysseus (Greek mythology) in literature; Heroes in literature; Mythology, Greek; Educational videos